A clinical trial evaluates the effect of pomegranate extract as a mouth wash for gingivitis in type 2 diabetic patients - Shayma Ghazi; Dilyar Ahmed Baban; Saif Monem Aziz (Erbil Dental Journal)
Background and Objectives: Type-2 diabetes mellitus (T2DM) is a systemic disease which have higher incidence of gingivitis and periodontitis. Pomegranate peel has higher content of phenolic compounds with potent anti-inflammatory, antioxidant and antibacterial activity. The aim is to evaluate the efficacy of pomegranate peel extract on the clinical and biochemical measures of (IL-1β) and the enzyme (AST) in saliva of (T2DM) patients suffering from gingivitis in comparison with chlorhexidine.